Component Matters: Paving the Roadmap toward Enhanced Electrocatalytic Performance of Graphitic C3N4‑Based Catalysts via Atomic Tuning - Pei, Zengxia; Gu, Jingxing; Wang, Yukun; Tang, Zijie; Liu, Zhuoxin; Huang, Yan; Huang, Yang; Zhao, Jingxiang; Chen, Zhongfang; Zhi, Chunyi (ACS nano, 2017)
Atomically precise understanding of componential influences is crucial for looking into the reaction mechanism and controlled synthesis of efficient electrocatalysts. Herein, by means of comprehensive experimental and theoretical studies, we carefully examine the effects of component dopants on the catalytic performance of graphitic C3N4 (g-C3N4)-based electrocatalysts. The g-C3N4 monoliths with three types of dopant elements (B, P, and S) embedded in different sites (either C or N) of the C–N skeleton are rationally designed and synthesized. The kinetics, intrinsic activity, charge-transfer process, and intermediate adsorption/desorption free energy of the selected catalysts in oxygen reduction reaction and hydrogen evolution reaction are investigated both experimentally and theoretically. We demonstrate that the component aspect within the g-C3N4 motifs has distinct and substantial effects on the corresponding electroactivities, and proper component element engineering can be a viable yet efficient protocol to render the metal-free composites as competent catalysts rivaling the metallic counterparts. We hope that this study may shed light on the empirical trial-and-error exploration in design and development of g-C3N4-based materials as well as other metal-free catalysts for energy-related electrocatalytic reactions.